Penerapan Model Pembelajaran Project Based Learning Berbasis STEAM Pada Pokok Pembahasan Aritmatika Sosial - Gahung, Veiren Sitovaya Noviany; Kaunang, Derel F.; Maukar, Marvel G. (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
The purpose of this study is to determine if the STEAM-based Project Based Learning learning model improves students' mathematics learning outcomes on the topic of social arithmetic in comparison to conventional learning models. Class VII A, who utilized the Conventional model, and Class VII C, who utilized the STEAM-based Project Based Learning learning model, served as the research subjects. Pretest Posttest Experiment Group Design is the research design for this quasi-experimental study. The two classes with 20 and 21 students, respectively, that comprised the research sample were VII A and VII C. Both classes were normal and homogeneous. A t-test is used for the data analysis test, and values are rejected before being accepted. As a result, students' learning outcomes have improved when employing the STEAM-based Project Based Learning learning model. Keywords: project-based learning, STEAM, learning outcomes